2005
DOI: 10.1111/j.1399-6576.2005.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of desflurane and sevoflurane on oxytocin‐induced contractions of isolated pregnant human myometrium

Abstract: Desflurane and sevoflurane at 0.5, 1 and 2 MAC inhibit the frequency and amplitude of myometrial contractions induced with oxytocin in a dose-dependent manner. However, desflurane inhibits the amplitude less than sevoflurane at 1 MAC. We suggest that 0.5 MAC of both agents and 1 MAC of desflurane may be safely used in the presence of oxytocin following delivery of the infant and placenta during Cesarean section without fear of uterine atony and hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 22 publications
0
27
0
1
Order By: Relevance
“…Recently, new computer software has made it possible to calculate the AUC [13][14][15]. Previous studies have found that sevofl urane reduces both the amplitude and frequency of myometrium contractions in myometrium isolated from humans [9,10] and rats [11,12]. Sevofl urane-induced myometrial relaxation has also been established using the AUC [13][14][15].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, new computer software has made it possible to calculate the AUC [13][14][15]. Previous studies have found that sevofl urane reduces both the amplitude and frequency of myometrium contractions in myometrium isolated from humans [9,10] and rats [11,12]. Sevofl urane-induced myometrial relaxation has also been established using the AUC [13][14][15].…”
Section: Discussionmentioning
confidence: 98%
“…The effect of drugs on myometrium contraction has been studied using isolated myometrial strips from humans [9,10] and rats [11,12]. The amplitude and frequency have traditionally been used as an index of myometrium contraction because they can be easily measured from analog data.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, sevoflurane increases ICP and cerebrovascular reactivity, and decreases cerebral perfusion 17 and uterine contractility. 18,19 We chose propofol because of its advantages of decreasing intracranial blood pressure and volume 20 and postoperative nausea. Succinylcholine and Syntocinon, a synthetic oxytocin, may not increase ICP and may be considered as safe drugs in this condition.…”
Section: Discussionmentioning
confidence: 99%
“…15 Uterine atony/blood loss: Volatile anesthetic agents cause dose-dependent myometrial relaxation. 16,17 Therefore, increasing the dose of volatile agent (to decrease the risk of awareness) may be associated with an increased risk of uterine atony and hemorrhage. Indeed, in seven of eight studies in which general was compared with neuraxial anesthesia and estimated blood loss (EBL) was reported as an outcome, EBL was lower in the neuraxial than the general anesthesia group.…”
mentioning
confidence: 99%